Knowledge Sharing and Organizational Culture: A Qualitative Study of Pakistan’s Banking Sector (Pakistan Business Review, 2025)
Purpose: The study aims to identify the impact of knowledge sharing mechanism and Organizational culture on the banking sector of Pakistan. Design/methodology/approach: For the purpose of this study qualitative research method was employed incorporating semi-structured interviews from employees in the banking industry. The present research is qualitative research and allowed the researcher to study experiences in greater depth and come up with the universal essence of experiences, so the phenomenological methodology was used to get profound understanding of OC and KS in banking sector of Pakistan. Findings: Findings of current research revealed that banking sector of Pakistan especially private sector is improving the quality of their services by focusing and improving their KS culture but in public sector government strongly affects its culture, policies and regulations. Research limitations/implications: Future research should aim for a larger and more diverse sample to generalize the findings. Furthermore, mixed-method approaches can be conducted to further validate the findings. The limited sample size of the present research may not represent the larger population. Originality/Value: Contribution of this study is to both practical and hypothetical bodies of knowledge. Practical contributions are related to the banking sector whereas hypothetical contributions are relevant to other businesses and firms that want to be successful through KS. Current research has made important contribution to the exiting literature in terms of OC and KS.